Comparative and international public administration: building intellectual bridges - Heady, Ferrel (1998)
A partial redirection is proposed for the activities of ASPA's Section on International and Comparative Administration (SICA) as it enters its second quarter century. Implicit in the SICA mission is the task of integrating the study and practice of comparative and international administration, but much remains to be done in bringing about closer collaboration than has been achieved in the past between specialists in these two subfields. - Reproduced
Keywords: Public administration